2020
DOI: 10.4236/abc.2020.102003
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Coordination Compounds of (±)-2-Amino-3-(4-Hydroxyphenyl)Propionic Acid, Mixed Ligand Complexes and Their Biological Activities

Abstract: Coordination compounds of (±)-2-amino-3-(4-hydroxyphenyl)propionic acid and their mixed ligand complexes with 1,10-phenantroline were synthesized, characterized using electronic and infrared spectral analyses and magnetic susceptibility. The compounds were evaluated for antimicrobial and antioxidant activities. Four different assays were applied for evaluating antioxidant capacity of the compounds. The results obtained indicated a diametric square planar geometry for both cobalt (±)-2-amino-3-(4-hydroxyphenyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…While working on the introduction to our personal article, we found that in 2020 alone, more than 50 papers were published, which describe the results of a study of the antimicrobial activity of copper complexes. During the preparation of the manuscript for submission a number of works [59][60][61][62][63][64][65][66][67][68][69] were published that were not included in the above analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While working on the introduction to our personal article, we found that in 2020 alone, more than 50 papers were published, which describe the results of a study of the antimicrobial activity of copper complexes. During the preparation of the manuscript for submission a number of works [59][60][61][62][63][64][65][66][67][68][69] were published that were not included in the above analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity for all the complexes was carried out using four assays namely; nitric oxide radical inhibition, ferric reducing antioxidant power (FRAP), ferrous ion-chelating ability and cupric ion reducing antioxidant capacity assays. The compounds were synthesized using an adaptation of previous method [23]. The equations of the reactions are given in Equations ( 1)- (6).…”
Section: Generalmentioning
confidence: 99%
“…Arouri et al (2021) synthesized the FeCl 4 (C 5 N 2 H 6 )(C 5 N 2 H 5 ) complex and characterized it by X-ray, IR, UV methods and applied it for various uses [14]. Iyelabola, Akinkunmi, and Akinade (2020) synthesized and characterized mixed ligand complexes of Co +2 , Ni +2 and Cu +2 with 1,10-phenantroline and (±)-2-amino-3-(4-hydroxyphenyl)propionic acid as ligands and reported their biological activities [15]. Moriguchi, Kawata, and Jalli (2021) synthesized a new hydrogen-bonded cobalt(II) complex and used the title complex for therapeutic applications [16].…”
Section: Introductionmentioning
confidence: 99%